A molybdenum alloy and preparation method thereof

By using nanohydride powder and molybdenum powder in molybdenum alloy and mixing treatment, sintering, rotary forging and recrystallization annealing processes, a heterostructure of molybdenum matrix and nano-strengthening phase was formed, and the poor room temperature ductility and oxygen segregation problems of molybdenum alloy are solved. , significantly improves its strength and ductility.

CN118773465BActive Publication Date: 2024-12-27INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411267937.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-27
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

Molybdenum alloys have poor ductility at room temperature, and impurities such as oxygen are prone to segregation onto the grain boundaries to weaken their strength, resulting in brittle fracture.

Method used

The nanotitanium hydride and nanozirconium hydride powder were mixed with molybdenum powder. Through sintering and multi-pass rotary forging and recrystallization annealing process, a heterostructure of the molybdenum matrix and the nano-strengthening phase was formed, and the nails at the relative grain boundaries were strengthened by nano-strengthening. The priming effect hinders the growth of grains and improves the strength and ductility of the alloy.

Benefits of technology

The room temperature yield strength and elongation of molybdenum alloys are significantly improved, and the problem of poor ductility of traditional molybdenum alloys is solved. At the same time, the oxygen content is reduced, the enhanced phase agglomeration and grain boundary oxygen agglomeration are avoided, and the comprehensive performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118773465B_ABST
    Figure CN118773465B_ABST
Patent Text Reader

Abstract

The present invention provides a molybdenum alloy and a preparation method thereof, which relates to the technical field of powder metallurgy nanostructure material preparation and includes the following steps: step 1) preparing a suspension, mixing the suspension with molybdenum powder, and obtaining a mixed powder after drying; step 2) sintering the mixed powder to obtain a sintered blank; wherein the microstructure of the sintered blank includes a molybdenum matrix and a nano-reinforced phase; step 3) performing multiple rotary forging treatments on the sintered blank to obtain a molybdenum alloy rod; step 4) performing recrystallization annealing on the molybdenum alloy rod, and obtaining a molybdenum alloy after cooling treatment; wherein the molybdenum matrix in the molybdenum alloy forms a heterogeneous structure of a mixture of coarse crystals and nano-crystals, and obtaining a molybdenum alloy after cooling treatment. The present invention uses a multi-pass rotary forging coordinated recrystallization annealing process, combined with the pinning effect of nano-reinforcement phases on grain boundaries, to enable the molybdenum alloy to obtain a heterogeneous structure of a mixture of coarse crystals and nano-crystals, thereby improving the strength and ductility of the molybdenum alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of powder metallurgy nanostructured material preparation, and specifically relates to a molybdenum alloy and a preparation method thereof. Background Art

[0002] Molybdenum is a refractory metal with a melting point of 2610℃, which can stably maintain a body-centered cubic structure without phase change. Molybdenum and molybdenum alloys are often used as candidate materials for key high-temperature applications such as fusion reactor components, missiles, turbines and rocket nozzles due to their excellent high-temperature strength, thermal stability, creep resistance and high thermal conductivity.

[0003] However, due to the ductile-brittle transition of molybdenum at room temperature, the deformation of the body-centered cubic structure of molybdenum is mainly through screw dislocation slip, which is difficult to activate below the ductile-brittle transition temperature, resulting in poor ductility of molybdenum alloys. In addition, some impurity solid solution elements, especially oxygen, are easy to segregate to the grain boundaries, thereby weakening its strength and causing brittle fracture. Summary of the invention

[0004] Therefore, the present invention provides a molybdenum alloy and a preparation method thereof, the main purpose of which is to provide a high-strength, high-toughness molybdenum alloy and a preparation method thereof.

[0005] In order to solve the above problems, the present invention provides a method for preparing a molybdenum alloy, comprising the following steps:

[0006] Step 1) preparing a suspension, mixing the suspension with molybdenum powder, and drying to obtain a mixed powder; the suspension includes nano titanium hydride powder and nano zirconium hydride powder;

[0007] Step 2) sintering the mixed powder to obtain a sintered blank; wherein the microstructure of the sintered blank includes a molybdenum matrix and a nano-reinforced phase;

[0008] Step 3) performing multiple rotary forging processes on the sintered blank to obtain a molybdenum alloy rod;

[0009] Step 4) performing recrystallization annealing on the molybdenum alloy rod and obtaining a molybdenum alloy after cooling treatment; wherein the molybdenum matrix in the molybdenum alloy forms a heterogeneous structure of a mixture of coarse crystals and nanocrystals.

[0010] Furthermore, in step 1), the preparation of the suspension includes:

[0011] A dispersant is added to a mixture containing nano titanium hydride powder, nano zirconium hydride powder and fructose, and then ultrasonic dispersion is performed to obtain a suspension.

[0012] Furthermore, the particle size of the nano titanium hydride powder is 50-100 nm; the particle size of the nano zirconium hydride powder is 50-100 nm.

[0013] Furthermore, the dispersant is one or more of polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG) and sodium dodecyl sulfate.

[0014] Furthermore, the porosity of the molybdenum powder is greater than 60%, and the average particle size of the molybdenum powder is less than 200 nm.

[0015] Further, the preparation steps of the molybdenum powder are as follows:

[0016] The molybdenum powder is obtained by reducing the composite molybdenum oxide powder; wherein the composite molybdenum oxide powder comprises molybdenum dioxide and molybdenum;

[0017] The average particle size of the composite molybdenum oxide powder is less than 200 nm.

[0018] Furthermore, the reduction treatment includes: performing multi-temperature stage reduction on the composite molybdenum oxide powder under a hydrogen atmosphere;

[0019] The multi-temperature stage reduction comprises: heating the composite molybdenum oxide powder to 350°C-450°C for 1-2 hours, then heating to 550°C-650°C for 1-2 hours, and then heating to 750°C-850°C for 1-2 hours; wherein the paving thickness of the composite molybdenum oxide powder is less than 10 mm.

[0020] Furthermore, in the step 1), the mixing process includes:

[0021] The suspension is stirred, and while stirring, the molybdenum powder is added to the suspension to obtain a mixed slurry, and then the mixed slurry is dried to obtain a mixed powder.

[0022] Furthermore, in the step 2), the sintering process includes: performing multi-temperature stage vacuum sintering on the mixed powder;

[0023] Among them, the multi-temperature stage vacuum sintering includes: heating the mixed powder to 800℃~1000℃ and sintering for 1~2 hours, then heating to 1000℃~1200℃ and sintering for 1~2 hours, then heating to 1400℃~1600℃ and sintering for 1~2 hours, and finally heating to 1800℃~2000℃ and sintering for 4~6 hours.

[0024] Furthermore, in the step 3), the total deformation of the multiple rotary forgings is 60% to 95%; wherein the deformation of each rotary forging is less than 25%;

[0025] The temperature of the multi-pass rotary forging process is 800℃~1400℃.

[0026] Further, in the step 4), the recrystallization annealing includes:

[0027] The molybdenum alloy rod is heated to 850°C-1050°C and kept warm for 0.1-1 hour; then heated to 1050°C-1250°C and kept warm for 0.1-1 hour; then heated to 1250°C-1350°C and kept warm for 0.1-1 hour.

[0028] On the other hand, the present invention provides a molybdenum alloy, which comprises the following components by mass percentage: Zr: 0.05%-0.15%, Ti: 0.1%-0.8%, C: 0.01%-0.02%, and the balance is Mo;

[0029] The molybdenum alloy is obtained by any of the preparation methods described above.

[0030] Furthermore, the structure of the molybdenum alloy includes a molybdenum matrix and a nano-strengthening phase; the nano-strengthening phase includes one or more of a nano-ZrC phase, a nano-TiC phase, a nano-ZrO2 phase and a nano-TiO2 phase.

[0031] Furthermore, the molybdenum matrix is ​​a heterogeneous structure, which includes coarse crystals and nano crystals; in the heterogeneous structure, the volume proportion of nano crystals is 15-35%, and the grain size of nano crystals is 50-500nm; the volume proportion of coarse crystals is 65-85%, and the grain size of coarse crystals is 2-5μm.

[0032] Furthermore, the yield strength of the molybdenum alloy at room temperature is greater than 800 MPa, and the elongation is greater than 30%.

[0033] The molybdenum alloy and the preparation method thereof provided by the present invention have the following beneficial effects:

[0034] 1. The present invention uses nano hydride powder as raw material, and an internal oxidation process occurs during the sintering process to form a nano-strengthening phase. Then, through a multi-pass rotary forging coordinated recrystallization annealing process, combined with the pinning effect of nano-strengthening on the grain boundary, the molybdenum alloy obtains a heterogeneous structure of coarse crystals and nano-crystals; the multi-pass rotary forging forms an uneven strain distribution in the matrix of the molybdenum alloy bar. When the annealing temperature is lower than the complete recrystallization temperature, recrystallization occurs in the area with high strain distribution. The nano-strengthening has an obvious pinning effect on the grain boundary, which can effectively hinder the growth of grains, thereby obtaining nano-crystals, and the matrix without recrystallization is still coarse crystals. Among them, nano-crystals provide high strength for the alloy, and coarse crystals provide toughness for the alloy. The two act synergistically when deformed, thereby greatly improving the strength and ductility of the molybdenum alloy, and solving the problem of poor room temperature ductility of traditional molybdenum alloys.

[0035] 2. The present invention uses composite molybdenum oxide powder as a molybdenum source, and while reducing production costs, obtains ultrafine molybdenum powder with low oxygen content, high dispersion and high porosity through multi-temperature stage reduction treatment, so that nano hydride is evenly distributed in the pores of the molybdenum powder, ensuring that the strengthening phase is evenly distributed inside the grains during the sintering process; the multi-temperature stage reduction treatment can induce nucleation of part of the molybdenum powder at low temperature and shorten the reduction time at high temperature; at the same time, the present invention introduces carbon through fructose instead of using carbon powder and graphite. Since fructose is a soluble substance, carbon can be more evenly distributed, which is conducive to the formation of nano ZrC phase and nano TiC phase.

[0036] 3. Furthermore, the present invention facilitates the mixing of fructose, nano hydride powder and molybdenum powder by means of dispersant coordinated ultrasonic dispersion, regulates the distribution of the strengthening phase from the source, and solves the phenomenon of strengthening phase agglomeration in traditional molybdenum alloys; at the same time, the formation of nano ZrO2 phase and nano TiO2 phase can avoid the segregation of oxygen elements in the matrix at the grain boundary, thereby ensuring the brittleness of the molybdenum alloy.

[0037] 4. Drying the mixed slurry by spray drying or freeze drying can avoid premature oxidation of hydrides, allow the internal oxidation process to proceed fully, and further reduce the oxygen content of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0039] Figure 1 This is a strain spectroscopy image of the molybdenum alloy rod prepared in Example 1 of the present invention;

[0040] Figure 2 This is a tensile curve diagram of the molybdenum alloy prepared in Example 1 of the present invention;

[0041] Figure 3 The electron microscope image of the microstructure of the molybdenum alloy prepared in Example 1 of the present invention;

[0042] Figure 4 The electron microscope image of the microstructure of the molybdenum alloy prepared in Comparative Example 1 of the present invention;

[0043] Figure 5 The electron microscope image of the microstructure of the molybdenum alloy prepared in Comparative Example 2 of the present invention;

[0044] Figure 6 This is an electron microscope image of the microstructure of the molybdenum alloy prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0045] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0046] The present invention provides a method for preparing a molybdenum alloy, comprising the following steps:

[0047] Step 1) preparing a suspension, mixing the suspension with molybdenum powder, and drying to obtain a mixed powder; the suspension includes nano titanium hydride powder and nano zirconium hydride powder;

[0048] Step 2) sintering the mixed powder to obtain a sintered blank; wherein the microstructure of the sintered blank includes a molybdenum matrix and a nano-reinforced phase;

[0049] Step 3) performing multiple rotary forging processes on the sintered blank to obtain a molybdenum alloy rod;

[0050] Step 4) performing recrystallization annealing on the molybdenum alloy rod and obtaining the molybdenum alloy after cooling treatment; wherein the molybdenum matrix in the molybdenum alloy forms a heterogeneous structure of a mixture of coarse crystals and nanocrystals.

[0051] Based on the above method, the present invention uses nano hydride particles as additives, aiming to form a strengthening phase during the internal oxidation process during the sintering process while reducing the oxygen content of the alloy. First, the surface of the hydride is modified by dispersion treatment to improve the wettability and dispersibility of the nano hydride; then the composite molybdenum oxide powder is reduced to adjust the porous structure of the molybdenum powder so as to achieve uniform mixing of the hydride and the molybdenum powder, laying the foundation for the uniform distribution of the internal oxidation products; then a multi-pass rotary forging and recrystallization annealing process is adopted, and the pinning effect of the nano-reinforcement phase formed by internal oxidation on the grain boundary is utilized to achieve a heterogeneous structure of coarse crystals and nano-crystals in the molybdenum alloy, which greatly improves the strength and ductility of the molybdenum alloy and solves the problem of poor ductility of traditional molybdenum alloys at room temperature.

[0052] Among them, the strain distribution of the molybdenum alloy rod after multiple rotary forging treatments is uneven. Recrystallization annealing is performed to make the part of the matrix with high strain energy preferentially recrystallize. The nano-strengthening has an obvious pinning effect on the grain boundary, which can effectively hinder the growth of grains, thereby obtaining nanocrystals; the matrix that has not undergone recrystallization is coarse crystals. Nanocrystals and coarse crystals have completely different flow stresses, which makes it impossible for the material to deform plastically freely. Dislocations need to be generated at the grain boundaries of coarse crystals to adapt, thereby producing a synergistic strengthening effect. As the deformation of the material increases, nanocrystals and coarse crystals undergo plastic deformation at the same time. The coarse crystals bear greater plastic strain than the nanocrystals, and a strain gradient is generated at the junction of the coarse crystals and nanocrystals, causing the material to undergo back stress work hardening, which can greatly improve the overall performance of the material.

[0053] In some embodiments, in step 1), preparing the suspension comprises:

[0054] A dispersant is added to a mixture containing nano titanium hydride powder, nano zirconium hydride powder and fructose, and then ultrasonic dispersion is performed to obtain a suspension.

[0055] In some embodiments, the particle size of the nano titanium hydride powder is 50-100 nm; the particle size of the nano zirconium hydride powder is 50-100 nm.

[0056] In some embodiments, the dispersant is one or more of polyvinylpyrrolidone (PVP), polyethylene glycol (PEG) and sodium dodecyl sulfate.

[0057] In some embodiments, the porosity of the molybdenum powder is greater than 60%, and the average particle size of the molybdenum powder is less than 200 nm.

[0058] In some embodiments, the preparation steps of molybdenum powder are as follows:

[0059] The composite molybdenum oxide powder is subjected to reduction treatment to obtain molybdenum powder; wherein the composite molybdenum oxide powder comprises molybdenum dioxide and molybdenum;

[0060] The average particle size of the composite molybdenum oxide powder is less than 200 nm.

[0061] In some embodiments, the reduction treatment includes: performing multi-temperature stage reduction on the composite molybdenum oxide powder in a hydrogen atmosphere;

[0062] Among them, the multi-temperature stage reduction includes: heating the composite molybdenum oxide powder to 450°C~650°C and keeping it warm for 1~2 hours, then heating it to 750°C~850°C and keeping it warm for 3~5 hours; the laying thickness of the composite molybdenum oxide powder is less than 10mm.

[0063] In some embodiments, in step 1), the mixing process includes:

[0064] The suspension is stirred, and while stirring, molybdenum powder is added to the suspension to obtain a mixed slurry, and then the mixed slurry is dried to obtain a mixed powder.

[0065] In some embodiments, in step 2), the sintering process includes: performing multi-temperature stage vacuum sintering on the mixed powder;

[0066] Among them, the multi-temperature stage vacuum sintering includes: heating the mixed powder to 800℃~1000℃ and sintering for 1~2 hours, then heating it to 1000℃~1200℃ and sintering for 1~2 hours, then heating it to 1400℃~1600℃ and sintering for 1~2 hours, and finally heating it to 1800℃~2000℃ and sintering for 4~6 hours.

[0067] In some embodiments, in step 3), the total deformation of the multiple rotary forgings is 60% to 95%; wherein the deformation of each rotary forging is less than 25%; excessive deformation of each rotary forging will cause cracks;

[0068] The temperature of the multi-pass rotary forging process is 800℃~1400℃.

[0069] In some embodiments, in step 4), the recrystallization annealing comprises:

[0070] Heat the molybdenum alloy rod to 850℃~1050℃, keep it warm for 0.1-1 hour; then heat it to 1050℃~1250℃, keep it warm for 0.1~1 hour, then heat it to 1250℃~1350℃, and keep it warm for 0.1~1 hour.

[0071] On the other hand, the present invention provides a molybdenum alloy, which comprises the following components by mass percentage: Zr: 0.05%~0.15%, Ti: 0.1%~0.8%, C: 0.01%~0.02%, and the balance is Mo;

[0072] The molybdenum alloy is obtained by any of the above preparation methods.

[0073] In some embodiments, the structure of the molybdenum alloy includes a molybdenum matrix and a nano-reinforced phase; the nano-reinforced phase includes one or more of a nano-ZrC phase, a nano-TiC phase, a nano-ZrO2 phase, and a nano-TiO2 phase.

[0074] During the sintering process, the titanium hydride and zirconium hydride in the raw materials react with the O in the matrix (i.e., internal oxidation reaction) to form nano ZrO2 phase and nano TiO2 phase, respectively, or react with the C in fructose to form ZrC phase and nano TiC phase, respectively; these nano reinforced phases interact with dislocations to enhance the strength of the alloy; at the same time, they can passivate cracks and hinder crack propagation; in addition, during the sintering and hot working process, the nano reinforced phases pin the grain boundaries to obtain a fine grain size (the grain boundaries of molybdenum alloys are prone to oxygen segregation; the higher the oxygen content, the more serious the deterioration of the material's performance; the finer the grains, the lower the oxygen content per unit grain boundary area, which is beneficial to reducing the brittleness of the molybdenum alloy).

[0075] In some embodiments, the molybdenum matrix is ​​a heterogeneous structure, and the heterogeneous structure includes coarse crystals and nano crystals; in the heterogeneous structure, the volume proportion of nano crystals is 15~35%, and the grain size of nano crystals is 50~500nm; the volume proportion of coarse crystals is 65~85%, and the grain size of coarse crystals is 2~5μm.

[0076] In some embodiments, the molybdenum alloy has a yield strength greater than 800 MPa and an elongation (at break) greater than 30% at room temperature.

[0077] The present invention is further described below in conjunction with embodiments and comparative examples.

[0078] Example 1

[0079] This embodiment provides a method for preparing a molybdenum alloy, comprising the following steps:

[0080] Step 1) preparing the raw materials, and then placing the raw materials in alcohol for ultrasonic dispersion with the aid of dispersants PVP and PEG to obtain a uniformly mixed suspension;

[0081] Among the raw materials, the mass of the nano zirconium hydride powder is 2 grams, the average particle size is 50nm, the mass of the nano titanium hydride powder is 8 grams, the average particle size is 50nm, and the mass of fructose is 0.7 grams; wherein, the frequency of ultrasonic dispersion is 25kHZ, and the time is 2 hours;

[0082] 1322.6 g of composite molybdenum oxide powder was taken, and the composite molybdenum oxide powder was heated to 450° C. for 2 hours in a hydrogen atmosphere, and then heated to 780° C. for 4 hours to obtain molybdenum powder with low oxygen content, high dispersion and high porosity; the porosity of the molybdenum powder was 75%, and the average particle size of the molybdenum powder was 150 nm;

[0083] The thickness of the composite molybdenum oxide powder is 3 mm.

[0084] The suspension is placed in a magnetic stirrer for stirring, and molybdenum powder is continuously added during stirring to obtain a uniformly dispersed mixed slurry, and then the mixed slurry is freeze-dried to obtain a mixed powder;

[0085] Step 2) pre-sintering the mixed powder at 1000° C., 1200° C., and 1600° C. for 1 hour in vacuum, and then sintering at 1850° C. for 6 hours in vacuum to obtain a sintered blank;

[0086] The magnetic stirrer rotates at 120 revolutions per minute, and the stirring time is 120 minutes. The vacuum sintering pressure is 40 MPa.

[0087] Step 3) In a protective atmosphere, the sintered blank is heated to 1300° C., kept at this temperature for 1 hour, and then subjected to multiple-pass rotary forging to obtain a molybdenum alloy rod; wherein the total deformation of the multiple-pass rotary forging is 85%;

[0088] Step 4) The molybdenum alloy rod is heated to 950°C and kept at this temperature for 0.5 hours, then the temperature is raised to 1250°C and kept at this temperature for 0.3 hours, and then the temperature is raised to 1300°C and kept at this temperature for 1 hour, to obtain a molybdenum alloy having nanocrystals and coarse crystals.

[0089] The strain distribution of the molybdenum alloy rod prepared in this embodiment is as follows: Figure 1 As shown, the tensile curve of the prepared molybdenum alloy is as follows Figure 2 As shown in the microstructure photos Figure 3 shown; from Figure 1 It can be seen that the strain distribution is uneven; its strain distribution is uneven; from Figure 2 It can be seen that the room temperature tensile strength of the molybdenum alloy prepared in this embodiment is 919.02.56MPa; Figure 3 It can be seen that the molybdenum alloy microstructure prepared in this embodiment is a heterogeneous structure, including 2-5μm coarse crystals and 50-500nm nanocrystals, wherein the volume proportion of nanocrystals is about 35%, and the volume proportion of coarse crystals is about 65%. The room temperature yield strength of the molybdenum alloy prepared in this embodiment is measured to be 895.51MPa, the elongation is 37.2%, and the oxygen content is 200ppm.

[0090] Example 2

[0091] This embodiment provides a method for preparing a molybdenum alloy, comprising the following steps:

[0092] Step 1) preparing the raw materials, and then placing the raw materials in alcohol for ultrasonic dispersion with the aid of dispersants PVP and PEG to obtain a uniformly mixed suspension;

[0093] Among the raw materials, the mass of the nano zirconium hydride powder is 2 grams, the average particle size is 50nm, the mass of the nano titanium hydride powder is 8 grams, the average particle size is 50nm, and the mass of fructose is 0.7 grams; wherein, the frequency of ultrasonic dispersion is 25kHZ, and the time is 2 hours;

[0094] 1322.6 g of composite molybdenum oxide powder was taken, and the composite molybdenum oxide powder was heated to 450° C. for 2 hours in a hydrogen atmosphere, and then heated to 750° C. for 3.5 hours to obtain molybdenum powder with low oxygen content, high dispersion and high porosity; the porosity of the molybdenum powder was 70%, and the average particle size of the molybdenum powder was 130 nm;

[0095] The thickness of the composite molybdenum oxide powder is 3 mm.

[0096] The suspension is placed in a magnetic stirrer for stirring, and molybdenum powder is continuously added during stirring to obtain a uniformly dispersed mixed slurry, and then the mixed slurry is freeze-dried to obtain a mixed powder;

[0097] Step 2) pre-sintering the mixed powder at 800° C., 1000° C., and 1400° C. for 1 hour in vacuum, and then sintering at 2000° C. for 6 hours in vacuum to obtain a sintered blank;

[0098] The magnetic stirrer rotates at 120 revolutions per minute, and the stirring time is 120 minutes. The vacuum sintering pressure is 40 MPa.

[0099] Step 3) In a protective atmosphere, the sintered blank is heated to 1300° C., kept at this temperature for 1 hour, and then subjected to multiple passes of rotary forging to obtain a molybdenum alloy rod; wherein the total deformation of the multiple passes of rotary forging is 75%;

[0100] Step 4) The molybdenum alloy rod is heated to 850°C and kept at this temperature for 0.5 hours, then the temperature is raised to 1050°C and kept at this temperature for 0.3 hours, and then the temperature is raised to 1250°C and kept at this temperature for 1 hour, to obtain a molybdenum alloy having nanocrystals and coarse crystals.

[0101] The molybdenum alloy prepared in this embodiment has a room temperature tensile strength of 927 MPa, a room temperature yield strength of 852.51 MPa, an elongation of 31%, and an oxygen content of 230 ppm.

[0102] Example 3

[0103] This embodiment provides a method for preparing a molybdenum alloy, comprising the following steps:

[0104] Step 1) preparing raw materials, and then placing the raw materials in alcohol for ultrasonic dispersion with the aid of a dispersant, sodium dodecyl sulfate, to obtain a uniformly mixed suspension;

[0105] Among the raw materials, the mass of the nano zirconium hydride powder is 2 grams, the average particle size is 50nm, the mass of the nano titanium hydride powder is 8 grams, the average particle size is 50nm, and the mass of fructose is 0.7 grams; wherein, the frequency of ultrasonic dispersion is 25kHZ, and the time is 2 hours;

[0106] 1322.6 g of composite molybdenum oxide powder was taken, and the composite molybdenum oxide powder was heated to 650° C. and kept for 1 hour under a hydrogen atmosphere, and then heated to 850° C. and kept for 3 hours to obtain a molybdenum powder with low oxygen content, high dispersion and high porosity;

[0107] The thickness of the composite molybdenum oxide powder is 3 mm.

[0108] The suspension is placed in a magnetic stirrer for stirring, and molybdenum powder is continuously added during stirring to obtain a uniformly dispersed mixed slurry, and then the mixed slurry is freeze-dried to obtain a mixed powder;

[0109] Step 2) pre-sintering the mixed powder at 800° C., 1200° C., and 1600° C. for 1 hour in vacuum, and then sintering at 1800° C. for 6 hours in vacuum to obtain a sintered blank;

[0110] The magnetic stirrer rotates at 120 revolutions per minute, and the stirring time is 120 minutes. The vacuum sintering pressure is 40 MPa.

[0111] Step 3) In a protective atmosphere, the sintered blank is heated to 1400° C., kept at this temperature for 1 hour, and then subjected to multiple-pass rotary forging to obtain a molybdenum alloy rod; wherein the total deformation of the multiple-pass rotary forging is 60%;

[0112] Step 4) The molybdenum alloy rod is heated to 1050°C and kept at this temperature for 0.5 hours, then the temperature is raised to 1150°C and kept at this temperature for 0.3 hours, and then the temperature is raised to 1350°C and kept at this temperature for 1 hour, to obtain a molybdenum alloy having nanocrystals and coarse crystals.

[0113] The molybdenum alloy prepared in this embodiment has a room temperature tensile strength of 887 MPa, a room temperature yield strength of 832.2 MPa, an elongation of 31.3%, and an oxygen content of 235 ppm.

[0114] Example 4

[0115] This embodiment provides a method for preparing a molybdenum alloy, comprising the following steps:

[0116] Step 1) preparing the raw materials, and then placing the raw materials in alcohol for ultrasonic dispersion with the aid of dispersants PVP and PEG to obtain a uniformly mixed suspension;

[0117] Among the raw materials, the mass of the nano zirconium hydride powder is 2 grams, the average particle size is 50nm, the mass of the nano titanium hydride powder is 8 grams, the average particle size is 50nm, and the mass of fructose is 0.7 grams; wherein, the frequency of ultrasonic dispersion is 25kHZ, and the time is 2 hours;

[0118] 1322.6 g of composite molybdenum oxide powder was taken, and the composite molybdenum oxide powder was heated to 650° C. and kept for 1 hour under a hydrogen atmosphere, and then heated to 750° C. and kept for 3.5 hours to obtain a molybdenum powder with low oxygen content, high dispersion and high porosity;

[0119] The thickness of the composite molybdenum oxide powder is 3 mm.

[0120] The suspension is placed in a magnetic stirrer for stirring, and molybdenum powder is continuously added during stirring to obtain a uniformly dispersed mixed slurry, and then the mixed slurry is freeze-dried to obtain a mixed powder;

[0121] Step 2) pre-sintering the mixed powder at 900° C., 1100° C., and 1500° C. for 1 hour in vacuum, and then sintering at 1900° C. for 6 hours in vacuum to obtain a sintered blank;

[0122] The magnetic stirrer rotates at 120 revolutions per minute, and the stirring time is 120 minutes. The vacuum sintering pressure is 40 MPa.

[0123] Step 3) In a protective atmosphere, the sintered blank is heated to 1400° C., kept at this temperature for 1 hour, and then subjected to multiple-pass rotary forging to obtain a molybdenum alloy rod; wherein the total deformation amount of the multiple-pass rotary forging is 95%;

[0124] Step 4) The molybdenum alloy rod is heated to 850°C and kept at this temperature for 0.5 hours, then the temperature is raised to 1050°C and kept at this temperature for 0.3 hours, and then the temperature is raised to 1250°C and kept at this temperature for 1 hour, to obtain a molybdenum alloy having nanocrystals and coarse crystals.

[0125] The molybdenum alloy prepared in this embodiment has a room temperature tensile strength of 907 MPa, a room temperature yield strength of 852.6 MPa, an elongation of 32.7%, and an oxygen content of 235 ppm.

[0126] Comparative Example 1

[0127] This comparative example provides a method for preparing a molybdenum alloy, comprising the following steps:

[0128] Step 1) preparing the raw materials, and then placing the raw materials in alcohol for ultrasonic dispersion with the aid of dispersants PVP and PEG to obtain a uniformly mixed suspension;

[0129] The raw materials include zirconium hydride powder, titanium hydride powder and fructose; wherein the mass of the zirconium hydride powder is 2 grams and the average particle size is 10 μm, the mass of the titanium hydride powder is 8 grams and the average particle size is 10 μm, and the mass of the fructose is 0.7 grams; wherein the frequency of ultrasonic dispersion is 25 kHz and the time is 2 hours;

[0130] 1322.6 g of composite molybdenum oxide powder was taken, and the composite molybdenum oxide powder was heated to 450° C. and kept for 2 hours under a hydrogen atmosphere, and then heated to 780° C. and kept for 4 hours to obtain a molybdenum powder with low oxygen content, high dispersion and high porosity;

[0131] The thickness of the composite molybdenum oxide powder is 3 mm.

[0132] The suspension is placed in a magnetic stirrer for stirring, and molybdenum powder is continuously added during stirring to obtain a uniformly dispersed mixed slurry, and then the mixed slurry is freeze-dried to obtain a mixed powder;

[0133] Step 2) pre-sintering the mixed powder at 1000° C., 1200° C., and 1600° C. for 1 hour in vacuum, and then sintering at 1850° C. for 6 hours in vacuum to obtain a sintered blank;

[0134] The magnetic stirrer rotates at 120 revolutions per minute, and the stirring time is 120 minutes. The vacuum sintering pressure is 40 MPa.

[0135] Step 3) In a protective atmosphere, the sintered blank is heated to 1300° C., kept at this temperature for 1 hour, and then subjected to multiple-pass rotary forging to obtain a molybdenum alloy rod; wherein the total deformation of the multiple-pass rotary forging is 85%;

[0136] Step 4) The molybdenum alloy rod is heated to 950°C and kept at this temperature for 0.5 hours, then the temperature is raised to 1300°C with the furnace and kept at this temperature for 0.3 hours, and then the temperature is raised to 1330°C with the furnace and kept at this temperature for 1 hour to obtain a molybdenum alloy.

[0137] The room temperature tensile strength of the molybdenum alloy prepared in this comparative example is 780.3MPa, the room temperature yield strength is 720.6MPa, the elongation is 13%, and the oxygen content is 700ppm. It can be seen that the room temperature tensile strength, room temperature yield strength and elongation of the molybdenum alloy are all low, while the oxygen content is high. The microstructure photo of the molybdenum alloy prepared in this comparative example is shown in FIG. Figure 4 As shown in the figure, it can be seen that the microstructure of the molybdenum alloy is a typical recrystallized structure, which leads to a decrease in the ductility of the molybdenum alloy. This is because the size of zirconium hydride and titanium hydride is relatively large. Under the premise of unchanged mass fraction, the volume fraction of the strengthening phase particles formed by internal oxidation is reduced, the deoxidation effect of the internal oxidation process on the matrix is ​​weakened, and the pinning ability of the strengthening phase particles on the grain boundary is weakened, so that the molybdenum alloy rod undergoes complete recrystallization during the annealing process, which deteriorates the performance of the material.

[0138] Comparative Example 2

[0139] This comparative example provides a method for preparing a molybdenum alloy, comprising the following steps:

[0140] Step 1) preparing the raw materials, and then placing the raw materials in alcohol for ultrasonic dispersion with the aid of dispersants PVP and PEG to obtain a uniformly mixed suspension;

[0141] Among the raw materials, the mass of the nano zirconium hydride powder is 2 grams, the average particle size is 50nm, the mass of the nano titanium hydride powder is 8 grams, the average particle size is 50nm, and the mass of fructose is 0.7 grams; wherein, the frequency of ultrasonic dispersion is 25kHZ, and the time is 2 hours;

[0142] 1322.6 g of composite molybdenum oxide powder was taken, and the composite molybdenum oxide powder was heated to 450° C. and kept for 2 hours under a hydrogen atmosphere, and then heated to 780° C. and kept for 4 hours to obtain a molybdenum powder with low oxygen content, high dispersion and high porosity;

[0143] The thickness of the composite molybdenum oxide powder is 3 mm.

[0144] The suspension is placed in a magnetic stirrer for stirring, and molybdenum powder is continuously added during stirring to obtain a uniformly dispersed mixed slurry, and then the mixed slurry is freeze-dried to obtain a mixed powder;

[0145] Step 2) pre-sintering the mixed powder at 1000° C., 1200° C., and 1600° C. for 1 hour in vacuum, and then sintering at 1850° C. for 6 hours in vacuum to obtain a sintered blank;

[0146] The magnetic stirrer rotates at 120 revolutions per minute, and the stirring time is 120 minutes. The vacuum sintering pressure is 40 MPa.

[0147] Step 3) In a protective atmosphere, the sintered blank is heated to 1300° C., kept at this temperature for 1 hour, and then subjected to multiple-pass rotary forging to obtain a molybdenum alloy rod; wherein the total deformation of the multiple-pass rotary forging is 85%;

[0148] Step 4) The molybdenum alloy rod is kept at 1100° C. for 1 hour to obtain a molybdenum alloy.

[0149] The room temperature tensile strength of the molybdenum alloy prepared in this comparative example is 820.6MPa, the room temperature yield strength is 768.5MPa, the elongation is 24.2%, and the oxygen content is 206ppm. It can be seen that the room temperature tensile strength, room temperature yield strength and elongation of the molybdenum alloy are all low. The microstructure photo of the molybdenum alloy prepared in this comparative example is shown in FIG. Figure 5 As shown, it can be seen that a heterogeneous structure of coarse crystals and nano crystals is not formed. This is because the stress relief annealing of the molybdenum alloy rod is carried out by the traditional process. The annealing temperature is in the stress relief annealing stage and does not reach the recrystallization temperature. Therefore, the microstructure of the heterogeneous structure of recrystallized nano crystals and coarse crystals cannot be obtained, resulting in low room temperature tensile strength, room temperature yield strength and elongation.

[0150] Comparative Example 3

[0151] This comparative example provides a method for preparing a molybdenum alloy, comprising the following steps:

[0152] Step 1) preparing the raw materials, and then placing the raw materials in alcohol for ultrasonic dispersion with the aid of dispersants PVP and PEG to obtain a uniformly mixed suspension;

[0153] Among the raw materials, the mass of the nano zirconium hydride powder is 2 grams, the average particle size is 50nm, the mass of the nano titanium hydride powder is 8 grams, the average particle size is 50nm, and the mass of fructose is 0.7 grams; wherein, the frequency of ultrasonic dispersion is 25kHZ, and the time is 2 hours;

[0154] 1322.6 g of composite molybdenum oxide powder was taken, and in a hydrogen atmosphere, the composite molybdenum oxide powder was heated to 450° C. for 2 hours, and then heated to 780° C. for 4 hours to obtain molybdenum powder with low oxygen content, high dispersion and high porosity;

[0155] The thickness of the composite molybdenum oxide powder is 3 mm.

[0156] The suspension is placed in a magnetic stirrer for stirring, and molybdenum powder is continuously added during stirring to obtain a uniformly dispersed mixed slurry, and the mixed slurry is freeze-dried to obtain a mixed powder;

[0157] Step 2) pre-sintering the mixed powder at 1000° C., 1200° C., and 1600° C. for 1 hour in vacuum, and then sintering at 1850° C. for 6 hours in vacuum to obtain a sintered blank;

[0158] The magnetic stirrer rotates at 120 revolutions per minute, and the stirring time is 120 minutes. The vacuum sintering pressure is 40 MPa.

[0159] Step 3) In a protective atmosphere, the sintered blank is heated to 1300° C., kept at this temperature for 1 hour, and then subjected to multiple passes of rotary forging to obtain a molybdenum alloy rod; wherein the total deformation of the multiple passes of rotary forging is 55%;

[0160] Step 4) The molybdenum alloy rod is kept at 1100° C. for 1 hour to obtain a molybdenum alloy.

[0161] The room temperature tensile strength of the molybdenum alloy prepared in this comparative example is 820.3MPa, the room temperature yield strength is 790.51MPa, the elongation is 24.2%, and the oxygen content is 200ppm. It can be seen that the room temperature tensile strength, room temperature yield strength and elongation of the molybdenum alloy are all low. The microstructure photo of the molybdenum alloy prepared in this comparative example is shown in FIG. Figure 6As shown in the figure, it can be seen that no heterogeneous structure of coarse-grained and nano-grained mixed has been formed. This is because the total deformation of the multi-pass rotary forging is low, resulting in a low dislocation density within the grains of the molybdenum alloy rod, and the recrystallization annealing cannot obtain the microstructure of the heterogeneous structure, resulting in low room temperature tensile strength, room temperature yield strength and elongation.

[0162] Comparative Example 4

[0163] This comparative example provides a method for preparing a molybdenum alloy, comprising the following steps:

[0164] Step 1) preparing the raw materials, and then placing the raw materials in alcohol for ultrasonic dispersion with the aid of dispersants PVP and PEG to obtain a uniformly mixed suspension;

[0165] Among the raw materials, the mass of the nano zirconium hydride powder is 2 grams, the average particle size is 50nm, the mass of the nano titanium hydride powder is 8 grams, the average particle size is 50nm, the mass of the carbon powder is 0.7 grams, the average particle size is 10μm; wherein, the frequency of ultrasonic dispersion is 25kHZ, and the time is 2 hours;

[0166] 1322.6 grams of composite molybdenum oxide powder was taken, and the composite molybdenum oxide powder was heated to 450° C. and kept for 2 hours in a hydrogen atmosphere, and then heated to 780° C. and kept for 4 hours to obtain molybdenum powder with low oxygen content, high dispersion and high porosity; wherein the paving thickness of the composite molybdenum oxide powder was 3 mm;

[0167] The suspension is placed in a magnetic stirrer for stirring, and molybdenum powder is continuously added during stirring to obtain a uniformly dispersed mixed slurry, and then the mixed slurry is freeze-dried to obtain a mixed powder;

[0168] Step 2) pre-sintering the mixed powder at 1000° C., 1200° C., and 1600° C. for 1 hour in vacuum, and then sintering at 1850° C. for 6 hours in vacuum to obtain a sintered blank;

[0169] The magnetic stirrer rotates at 120 revolutions per minute, and the stirring time is 120 minutes. The vacuum sintering pressure is 40 MPa.

[0170] Step 3) In a protective atmosphere, the sintered blank is heated to 1300° C., kept at this temperature for 1 hour, and then subjected to multiple-pass rotary forging to obtain a molybdenum alloy rod; wherein the total deformation of the multiple-pass rotary forging is 85%;

[0171] Step 4) The molybdenum alloy rod is heated to 950°C and kept at this temperature for 0.5 hours, then the temperature is raised to 1250°C and kept at this temperature for 0.3 hours, and then the temperature is raised to 1300°C and kept at this temperature for 1 hour, to obtain a molybdenum alloy having nanocrystals and coarse crystals.

[0172] The room temperature tensile strength of the molybdenum alloy prepared in this comparative example is 830.7MPa, the room temperature yield strength is 760.4MPa, the elongation is 18.2%, and the oxygen content is 300ppm. It can be seen that the room temperature tensile strength, room temperature yield strength and elongation of the molybdenum alloy are all low, and the oxygen content is high. This is because carbon powder is used to introduce carbon, the carbon distribution in the matrix is ​​uneven and the deoxidation effect is poor, and the oxygen content in the molybdenum alloy is too high, which causes the grain boundary embrittlement and the performance degradation.

[0173] It is easy for those skilled in the art to understand that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.

[0174] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present invention. These improvements and variations should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a molybdenum alloy, characterized in that: The following steps are involved: Step 1) preparing a suspension, mixing the suspension with molybdenum powder, and drying to obtain a mixed powder; the suspension includes nano titanium hydride powder and nano zirconium hydride powder; Step 2) sintering the mixed powder to obtain a sintered blank; wherein the microstructure of the sintered blank includes a molybdenum matrix and a nano-reinforced phase; Step 3) performing multiple rotary forging processes on the sintered blank to obtain a molybdenum alloy rod; Step 4) performing recrystallization annealing on the molybdenum alloy rod, and obtaining a molybdenum alloy after cooling treatment; wherein the molybdenum matrix in the molybdenum alloy forms a heterogeneous structure of a mixture of coarse crystals and nanocrystals; The total deformation of the multi-pass rotary forging is 60% to 95%; the deformation of each rotary forging is less than 25%; the temperature of the multi-pass rotary forging is 800°C to 1400°C; The recrystallization annealing comprises: The molybdenum alloy rod is heated to 850°C-1050°C and kept warm for 0.1-1 hour; then heated to 1050°C-1250°C and kept warm for 0.1-1 hour; then heated to 1250°C-1350°C and kept warm for 0.1-1 hour.

2. The method for preparing a molybdenum alloy according to claim 1, wherein In the step 1), the preparation of the suspension comprises: A dispersant is added to a mixture containing nano titanium hydride powder, nano zirconium hydride powder and fructose, and then ultrasonic dispersion is performed to obtain a suspension.

3. The method for preparing a molybdenum alloy according to claim 2, characterized in that: The particle size of the nano titanium hydride powder is 50-100 nm; the particle size of the nano zirconium hydride powder is 50-100 nm.

4. The method for preparing a molybdenum alloy according to claim 2, wherein: The dispersant is one or more of polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG) and sodium lauryl sulfate.

5. The method for preparing a molybdenum alloy according to claim 1, characterized in that: The porosity of the molybdenum powder is greater than 60%, and the average particle size of the molybdenum powder is less than 200nm.

6. The method for preparing a molybdenum alloy according to any one of claims 1 to 5, characterized in that: The preparation steps of the molybdenum powder are as follows: The molybdenum powder is obtained by reducing the composite molybdenum oxide powder; wherein the composite molybdenum oxide powder comprises molybdenum dioxide and molybdenum; The average particle size of the composite molybdenum oxide powder is less than 200 nm.

7. The method for preparing a molybdenum alloy according to claim 6, characterized in that: The reduction treatment comprises: performing multi-temperature stage reduction on the composite molybdenum oxide powder in a hydrogen atmosphere; The multi-temperature stage reduction comprises: heating the composite molybdenum oxide powder to 450°C-650°C for 1-2 hours, and then heating to 750°C-850°C for 3-5 hours; wherein the paving thickness of the composite molybdenum oxide powder is less than 10 mm.

8. The method for preparing a molybdenum alloy according to claim 1, characterized in that: In the step 1), the mixing process includes: The suspension is stirred, and while stirring, the molybdenum powder is added to the suspension to obtain a mixed slurry, and then the mixed slurry is dried to obtain a mixed powder.

9. The method for preparing a molybdenum alloy according to claim 1 or 8, characterized in that: In the step 2), the sintering process includes: performing multi-temperature stage vacuum sintering on the mixed powder; Among them, the multi-temperature stage vacuum sintering includes: heating the mixed powder to 800℃~1000℃ and sintering for 1~2 hours, then heating to 1000℃~1200℃ and sintering for 1~2 hours, then heating to 1400℃~1600℃ and sintering for 1~2 hours, and finally heating to 1800℃~2000℃ and sintering for 4~6 hours.

10. A molybdenum alloy, characterized in that: The molybdenum alloy comprises the following components by mass percentage: Zr: 0.05%-0.15%, Ti: 0.1%-0.8%, C: 0.01%-0.02%, and the balance is Mo; The molybdenum alloy is obtained by the preparation method described in any one of claims 1 to 9.

11. The molybdenum alloy according to claim 10, characterized in that The structure of the molybdenum alloy includes a molybdenum matrix and a nano-strengthening phase; the nano-strengthening phase includes one or more of a nano-ZrC phase, a nano-TiC phase, a nano-ZrO2 phase and a nano-TiO2 phase.

12. The molybdenum alloy according to claim 10, characterized in that The molybdenum matrix is ​​a heterogeneous structure, which includes coarse crystals and nano crystals; in the heterogeneous structure, the volume proportion of nano crystals is 15-35%, and the grain size of nano crystals is 50-500nm; the volume proportion of coarse crystals is 65-85%, and the grain size of coarse crystals is 2-5μm.

13. The molybdenum alloy according to any one of claims 10 to 12, characterized in that: The yield strength of the molybdenum alloy at room temperature is greater than 800 MPa and the elongation is greater than 30%.

Citation Information

Patent Citations

  • Method for rotary swaging multielement composite electron emission material of rare earth tungsten

    CN101049627A

  • Preparation method of molybdenum powder

    CN101642817A

  • Method for preparing large powder metallurgy TZM blank with uniform carbon and oxygen distribution

    CN101934372A

  • Powder metal forging and method and apparatus of manufacture

    US20100083782A1

  • Forged aluminum alloy spiral parts and method of fabrication thereof

    US4838936A